Surfactant Assisted In Situ Synthesis of Nanofibrillated Cellulose/Polymethylsilsesquioxane Aerogel for Tuning Its Thermal Performance. Issue 2 (23rd January 2023) - Gupta, Pragya; Sathwane, Manoj; Chhajed, Monika; Verma, Chhavi; Grohens, Yves; Seantier, Bastien; Agrawal, Ashish K.; Maji, Pradip K.
Abstract : Back Cover : In article 2200628, Pradip K. Maji and co‐worker show that the thermal conductivity depends upon solid and gaseous conductivity. The red and blue color gradients in aerogel slab distinguish hot and cold region. Green color fibers and spherical particles symbolize nanofibrillated cellulose and polymethylsilsesquioxane, respectively. The navy blue color air molecules diffuse into aerogel pores due to Knudsen effect. The structure of aerogel slab represents the thermal insulator.